Borehole heat exchangers in coastal areas may reduce heatwave seagrass loss - Rotman Criollo; Víctor Vilarrasa; Alejandro Orfila; Núria Marbà; Angels Fernández-Mora (Geoscience Letters)
Abstract Mitigation of climate change, implies, among other measures, the increase on the use of carbon-free energy sources, ensuring a zero environmental footprint. Borehole heat exchangers (BHE), a renewable heat source from the ground used for thermal regulation of infrastructures, could significantly reduce CO2 emissions. Yet, BHE perturbs groundwater temperature by heating and cooling the ground in summer and winter, respectively, which may alter the temperature of Sea Groundwater Discharges. We propose a methodology to strategically locate BHE to discharge cooler temperatures into the sea during summer, alleviating the extreme marine temperatures occurring during marine heatwaves around the groundwater discharge areas, and ensuring a thermal refuge for temperature-sensitive coastal ecosystems. This study opens a new avenue to accomplish the climate targets of the Paris Agreement and mitigate the negative effects of global warming on coastal ecosystems.